Employee productivity in Indonesia's Port Industry: Do Occupational Safety and Health Programs and work discipline matter? Evidence from a case study of PT Pelabuhan Indonesia (Persero) Regional 4, Makassar - Muhammad Umar Data; Wa Irna; Muhammad Dedy Miswar; Sigit Sugiarto (Universitas Nusa Cendana, 2026)
Employee productivity plays a fundamental role in enhancing organizational performance, particularly within the port industry, where operational efficiency and dependable service delivery are essential for achieving organizational objectives. This study investigates the effects of Occupational Safety and Health (OSH) programs and work discipline on employee productivity at PT Pelabuhan Indonesia (Persero) Regional 4 Makassar. Adopting a quantitative research approach, data were collected from employees in the Operations and Engineering Division using purposive sampling and analyzed through multiple linear regression to evaluate the influence of the independent variables on employee productivity. The findings indicate that OSH programs do not exert a significant influence on employee productivity, whereas work discipline positively contributes to improving employee productivity. Furthermore, the combined effect of OSH programs and work discipline provides substantial explanatory power in understanding variations in employee productivity. These findings suggest that in organizations with well-established safety management systems, productivity is influenced more strongly by behavioral and managerial factors, particularly employee discipline, than by the direct implementation of OSH initiatives. This study contributes to the human resource management and occupational safety literature by providing empirical evidence from the port industry. In addition, it offers practical implications for managers seeking to enhance employee productivity by strengthening work discipline while maintaining and continuously improving sustainable occupational safety and health management systems. Keywords: Employee Productivity; Occupational Safety and Health; Work Discipline; Human Resource Management; Port Industry